Effect of fermented restaurant waste meal addition on growth performance of pangasius catfish (Pangasius pangasius) for promoting sustainable aquaculture - Andriani Yuli; Iskandar; Pratama Rusky I.; Dwi Cahya Muhamad; Prima Mochamad Galuh N. (BIO Web of Conferences)
This study evaluates the use of fermented restaurant waste flour (FRWF) in artificial feed for improving the growth performance of catfish fry ( Pangasius pangasius). Restaurant waste, containing 10.89% protein, 9.70% fat, 0.39% phosphorus, and 0.08% calcium and 9.13% crude fiber, was fermented to enhance its nutritional value and determine its potential as a cost-effective feed ingredient. The research identified the optimal fermentation duration and FRWF inclusion rate through a completely randomized design with five treatments (0%, 10%, 20%, 30%, and 40% FRWF) and three replicates each. Parameters assessed included fermentation outcomes, daily growth, survival rate, and water quality. A seven-day fermentation period was optimal, yielding 25.38% protein, 15.97% moisture, and 4302 Kcal/kg energy. The 40% FRWF inclusion achieved the highest growth rate (1.93%/day) and acceptable survival rates (80–95%). Water quality parameters, including temperature (25.8°C), dissolved oxygen (4.80 mg/L), pH (7.15), and ammonia (0.03 mg/L), remained within suitable ranges. These findings suggest that incorporating fermented restaurant waste into fish feed can enhance growth performance while maintaining water quality, presenting a sustainable alternative for reducing feed costs in aquaculture.